A kind of anti-seepage and crack-resistant large-volume concrete and preparation method thereof

By modifying the combination formula of blast furnace slag powder, sodium acetate, expanded perlite water-absorbing aggregate and self-repaired polyvinyl alcohol fiber, the problem of leakage and cracking of underground engineering concrete is solved, and the excellent anti-seepage and cracking resistance of concrete is achieved. and structural durability improves.

CN118005336BActive Publication Date: 2025-01-03JIANGSU CHINA CONSTR COMMERCIAL CONCRETE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311820250.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2025-01-03
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

Underground engineering concrete is prone to leakage and cracking, resulting in reduced structural stability and shortened service life, making it difficult to effectively prevent and control the existing technology.

Method used

Using a combination formula including modified blast furnace slag powder, sodium acetate, expanded perlite water-absorbing aggregate and self-healing polyvinyl alcohol fiber, the synergistic effect of hydrophobicity, compactness, water-absorbing and self-repairing properties improves the anti-seepage of concrete Crack resistance.

Benefits of technology

It significantly improves the anti-seepage and crack resistance of concrete, extends the service life of the structure, reduces maintenance costs, and enhances the safety and durability of underground projects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004633779810000081
    Figure BDA0004633779810000081
Patent Text Reader

Abstract

The present invention discloses an anti-seepage and anti-cracking mass concrete and a preparation method thereof, and belongs to the technical field of concrete. The concrete comprises the following components in parts by weight: 410-440 parts of cementitious materials, 40-60 parts of modified blast furnace slag powder, 5-8 parts of sodium acetate, 720-760 parts of sand, 130-160 parts of expanded perlite water-absorbing aggregate, 900-950 parts of crushed stone, 5-8 parts of water-reducing agent, 140-155 parts of water, 1-2 parts of self-repairing polyvinyl alcohol fiber, and 0.8-1.4 parts of tragacanth; the modified blast furnace slag powder is obtained by mixing blast furnace slag and stearic acid and ball milling. The present invention synergistically improves the anti-seepage and anti-cracking properties of concrete by modified blast furnace slag powder, sodium acetate, expanded perlite water-absorbing aggregate and self-repairing polyvinyl alcohol fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and in particular relates to an anti-seepage and crack-resistant large-volume concrete and a preparation method thereof. Background Art

[0002] At present, my country has become the world's largest market for subway rail transit construction. However, with the rapid development of urban rail transit construction, the accompanying engineering safety issues have also been increasingly valued. Due to the complexity of underground projects, coupled with the requirements of materials and large-volume construction, subway underground concrete structures are prone to leakage, cracking and other defects. Once underground engineering concrete leaks, it will destroy the overall stability of the structure, reduce the functions of various facilities in the underground project (such as electrical facilities), and shorten the service life of the concrete structure. In addition, underground engineering water leakage not only wastes huge amounts of engineering construction funds, but also requires huge investment in rework, repairs, and maintenance, and the effect is poor. Therefore, how to prevent and control the cracking and leakage of large-volume concrete in underground projects has very important engineering application value.

[0003] The main reasons for leakage in underground structural projects are: (1) insufficient concrete density; (2) easy cracking of concrete. On the one hand, ordinary concrete has natural hydrophilicity, and the hydrophilic contact angles of the outer layer and the inner layer are small and the hydrophobicity is poor, which makes it easy for water to penetrate into the interior. The concrete has poor density and many harmful pores inside. Water can easily migrate inward along the channels. In addition, corrosive water sources or harmful chemicals invade and damage the structure. Under the influence of multiple factors, the concrete has poor impermeability and is prone to water leakage. On the other hand, due to the influence of factors such as the formula design of concrete materials and the high hydration heat of large-volume concrete, the risk of cracking in underground concrete structures has increased significantly, and shrinkage cracking and even through cracks are prone to occur. Under the coupling effect of the above two factors, underground concrete is ultimately prone to cracking and leakage, which seriously affects the durability of concrete and the safety of structural use.

[0004] In order to solve the leakage problem of underground structural engineering, the existing technologies mainly carry out anti-seepage and anti-cracking from the following aspects: (1) adding hydrophobic agents to improve the anti-seepage performance of concrete. Although the internal addition of hydrophobic agents can make the concrete hydrophobic both inside and outside, it has an adverse effect on the strength of the concrete; (2) from the perspective of concrete density, anti-seepage is achieved. However, since concrete is a multi-phase material, it is impossible to achieve ideal absolute density, and the problem of water penetrating through capillaries and harmful pores during the service of concrete is not solved; (3) using fibers to enhance the anti-cracking performance, and using self-healing materials such as repair capsules to repair cracks, but the preparation process of the repair capsules is complicated. At the same time, these two materials need to be added separately when mixing the concrete, which is time-consuming and labor-intensive, and the anti-cracking and repair effects are average.

[0005] Based on the above analysis, in order to prevent leakage in underground structural engineering, it is necessary to make systematic multi-scale considerations in the design of concrete materials so that the concrete's anti-seepage and anti-cracking effects can reach the best state, thereby improving the safety of engineering structure use and extending its service life. Summary of the invention

[0006] In view of the deficiencies of the above-mentioned prior art, one of the objects of the present invention is to provide a large-volume anti-seepage and crack-resistant concrete. Under the synergistic effect of various components, the anti-seepage and crack-resistant properties of the concrete are comprehensively improved from four aspects of drainage, resistance, absorption and prevention, so that the concrete has excellent anti-seepage and crack-resistant properties and structural durability, thereby solving the problem that traditional underground engineering structure concrete is prone to cracking and leakage.

[0007] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0008] A seepage-proof and crack-resistant mass concrete, comprising the following components in parts by weight: 410-440 parts of cementitious material, 40-60 parts of modified blast furnace slag powder, 5-8 parts of sodium acetate, 720-760 parts of sand, 130-160 parts of expanded perlite water-absorbing aggregate, 900-950 parts of crushed stone, 5-8 parts of water reducer, 140-155 parts of water, 1-2 parts of self-repairing polyvinyl alcohol fiber, and 0.8-1.4 parts of tragacanth gum;

[0009] The modified blast furnace slag powder is obtained by mixing blast furnace slag and stearic acid and then ball milling.

[0010] The concrete of the present invention, under the synergistic effect of each component, comprehensively improves the anti-seepage and anti-cracking properties of concrete from four aspects: drainage, resistance, absorption and prevention. Sodium acetate and modified blast furnace slag powder are used to synergistically improve the hydrophobicity and compactness of concrete, so that the concrete is hydrophobic both on the outside and inside, and the internal structure is dense, achieving "drainage" and "resistance", as the first anti-seepage defense line; the expanded perlite water-absorbing aggregate absorbs the water that penetrates into the concrete in the later stage, avoiding the migration and leakage of water to the inner wall, achieving "absorption", as the second anti-seepage defense line; self-repairing polyvinyl alcohol fiber is used to improve the crack resistance of concrete, and when cracks occur, the seepage water can be absorbed and blocked, avoiding the expansion of cracks and further infiltration of water, achieving "prevention", as the third anti-seepage defense line.

[0011] The mechanism by which sodium acetate and modified blast furnace slag powder synergistically improve the hydrophobicity and compactness of concrete is as follows: sodium acetate will hydrolyze in concrete, and -CH 3It can replace the -OH group in concrete and combine with the silicon atoms in cement to form hydrophobic organosilicon bonds, thereby improving the hydrophobicity of concrete. The activation of blast furnace slag can be promoted by ball milling, and the blast furnace slag powder is used as a physical carrier to mechanically coat the surface of the blast furnace slag powder with stearic acid. Stearic acid is adsorbed on the surface of the blast furnace slag powder to form hydrophobic particles of blast furnace slag powder, which reduces the surface energy of concrete and improves the overall hydrophobicity of concrete. On the other hand, the Na + Reacts with free water to form a sodium hydroxide (NaOH) complex; the surface morphology of blast furnace slag powder is relatively irregular, and it is difficult for stearic acid to completely cover it during ball milling, and there are uncovered points or surfaces. Under the stimulation of NaOH formed by the hydrolysis of sodium acetate, the uncovered surface of blast furnace slag powder will form more CSH gel and ettringite (AFt) crystals in the concrete, filling the pores and improving the density of the concrete.

[0012] Tragacanth gum has the property of forming a gel when in contact with water, which can promote the dispersion of cementitious materials during the mixing process, thereby improving fluidity. After pouring construction, the gel property of tragacanth gum can form a flexible network structure in the concrete, which helps to disperse and absorb stress caused by temperature changes and shrinkage, thereby reducing the formation of cracks.

[0013] Preferably, the mass of the stearic acid is 0.3% to 0.5% of the mass of the blast furnace slag. When the mass of the stearic acid is within the range defined in the present invention, the concrete can have good hydrophobicity and compactness.

[0014] In the present invention, the particle size of the expanded perlite water-absorbing aggregate is 5 to 10 mm, and the water absorption rate is 14% to 18%.

[0015] In the present invention, the preparation method of the expanded perlite water-absorbing aggregate comprises the following steps:

[0016] S1. dissolving corn gluten in an ethanol solution, adding a plasticizer, and stirring to obtain a hydrophobic coating solution;

[0017] S2. The expanded perlite and mannitol are mixed evenly at 60-70° C. to coat the surface of the expanded perlite with mannitol to obtain coated particles, and then the coated particles are immersed in the hydrophobic coating solution of step S1, and the expanded perlite water-absorbing aggregate is obtained after being taken out and allowed to stand and dry.

[0018] The mechanism of action of the expanded perlite water-absorbing aggregate of the present invention is as follows: the present invention utilizes corn protein to form a hard, smooth, hydrophobic coating film on the surface of the expanded perlite, which is thermally stable, almost insoluble in water, and soluble in an alkaline aqueous solution with a pH value of more than 11.5, so the coated expanded perlite basically does not absorb water in the early stage of concrete mixing and coagulation; as the alkalinity inside the concrete increases due to continuous hydration, when the hydration reaches the peak, the alkalinity inside the concrete rises to more than 12, and the corn protein begins to dissolve. At this time, most of the mixing water in the concrete has been consumed due to participation in hydration, so that the expanded perlite can still maintain a relatively dry state to maintain its good water absorption capacity during the service of the concrete. During the service of the concrete, when a small amount of water breaks through the hydrophobic layer generated by sodium acetate and modified blast furnace slag powder and enters the interior of the concrete through capillaries or harmful holes, the expanded perlite begins to absorb water to prevent water from leaking to the inner wall, and releases water when it is relatively dry to avoid long-term water storage inside. In the process, sodium acetate can be used as a buffer to help stabilize the pH value of the concrete. In addition, the present invention uses mannitol to wrap the surface of expanded perlite, so that the expanded perlite after the corn protein coating film is dissolved can be kept in a dry state; at the same time, the dissolution heat of mannitol is negative, and it has an endothermic effect. When the corn protein hydrophobic coating is dissolved, the hydration heat inside the concrete also reaches a high level. At this time, mannitol contacts with water, which can reduce the heat release of cement-based hydration, and effectively reduce the temperature rise and shrinkage cracking inside the large-volume concrete; further, mannitol has a chelating effect. When the corn protein is hydrolyzed, a certain gap is generated at the interface between the expanded perlite and the cement-based, and mannitol and the free Fe in the concrete 2+ 、Al 3+ , Ca 2+ Metal ions can form complex salts, fill interface voids, optimize the interface transition zone between expanded perlite and cement-based materials, and improve the strength and density of concrete.

[0019] Preferably, in step S1, the mass ratio of the corn protein, the ethanol solution and the plasticizer is (0.5-1.0):9.5:(0.1-0.2), and the mass concentration of the ethanol solution is 60%-92%.

[0020] Preferably, in step S2, the mass ratio of the expanded perlite to mannitol is 1:(0.1-0.2).

[0021] Preferably, in step S2, the coated particles are immersed in the hydrophobic coating solution for 20 to 30 minutes, taken out and allowed to stand and dry, immersed again for 20 to 30 minutes, taken out and allowed to stand and dry to obtain the expanded perlite water-absorbing aggregate.

[0022] In the present invention, the preparation method of the self-repairing polyvinyl alcohol fiber has the following steps: the polyvinyl alcohol fiber is rinsed with deionized water, and after drying, the fiber is immersed in an arabic gum aqueous solution, taken out and added to a mixed powder of white schizonepeta gum and magnesium fluorosilicate, stirred evenly, and then taken out and surface encapsulated with a polystyrene and polylactic acid blend to obtain the obtained fiber.

[0023] The mechanism of action of the self-repairing polyvinyl alcohol fiber of the present invention is as follows: polyvinyl alcohol fiber can improve the crack resistance of concrete. The present invention uses gum arabic to adhere the self-repairing agent composed of white radix gelatin and magnesium fluorosilicate to the surface of polyvinyl alcohol fiber. When cracks appear on the surface of concrete, water penetrates inward through the cracks. As the cracks expand, the fiber encapsulation outer shell is destroyed. The white radix gelatin encapsulated inside expands with water to form a gel to seal the cracks, and forms a highly viscous adhesive film to connect the concrete on both sides of the cracks, thereby slowing down the expansion of stress. Furthermore, the present invention uses magnesium fluorosilicate to promote the Ca in concrete. 2+ The dissolution of Ca 2+ It interacts with the hydroxyl groups in the white radix glue to form ionic crosslinks, thus increasing the strength of the gel formed by the white radix glue. Under the synergistic effect of magnesium fluorosilicate and white radix glue, a high-strength, high-viscosity gel can be formed, which can effectively seal cracks and slow down stress expansion.

[0024] In the above technical solution, the concentration of the gum arabic aqueous solution can be 20% to 30%, such as 20%, 25%, 30%, etc. The mass ratio of the white schizonepeta gum to the magnesium fluorosilicate is 100:(6-8).

[0025] In the present invention, the cementitious material comprises cement, fly ash and silica fume in a mass ratio of (340-360):(55-70):(10-15).

[0026] In the present invention, the method for preparing the anti-seepage and anti-cracking mass concrete comprises the following steps:

[0027] M1. Weigh each component by weight;

[0028] M2. The sodium acetate, modified blast furnace slag powder, 1 / 4 water reducer and 1 / 4 water are mixed evenly, and then the cementitious material, sand, gravel, tragacanth gum, 2 / 4 water reducer and 2 / 4 water are added and mixed evenly, and then the expanded perlite water-absorbing aggregate, self-healing polyvinyl alcohol fiber, 1 / 4 water reducer and 1 / 4 water are added and mixed evenly to obtain concrete slurry.

[0029] Compared with the prior art, the present invention is beneficial in that:

[0030] (1) The present invention synergistically improves the anti-seepage and anti-cracking properties of concrete by modified blast furnace slag powder, sodium acetate, expanded perlite water-absorbing aggregate and self-repairing polyvinyl alcohol fiber.

[0031] (2) The modified blast furnace slag powder and sodium acetate obtained by mixing and ball milling blast furnace slag and stearic acid in the present invention can synergistically improve the hydrophobicity and compactness of concrete.

[0032] (3) The present invention utilizes corn protein to form a hydrophobic coating on the surface of expanded perlite, thereby reducing the amount of water absorbed by the expanded perlite in the early stage of concrete mixing and setting, so that the expanded perlite can maintain excellent water absorption function during the service of concrete, absorb moisture that breaks through the hydrophobic layer and enters the interior of the concrete, and release the moisture when it is relatively dry; at the same time, mannitol is used to keep the expanded perlite dry, reduce the heat release of cement-based hydration, reduce the temperature rise and shrinkage cracking inside the large-volume concrete, fill the interface gap, optimize the interface transition zone between the expanded perlite and the cement-based material, and improve the strength and density of the concrete.

[0033] (4) The present invention utilizes white radix gelatin and magnesium fluorosilicate to modify polyvinyl alcohol fiber, so that the polyvinyl alcohol fiber has the function of repairing cracks when cracks occur in concrete, thereby improving the anti-seepage and anti-cracking performance of concrete. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In the following examples and comparative examples, the cement is ordinary Portland cement P·O 42.5; the sand is natural river sand with a fineness modulus of 2.8-3.0; the crushed stone is basalt with a particle size of 5-20 mm and an apparent density of 2600-2700 kg / m 3 , crushing value ≤12%; the water reducer is polycarboxylic acid water reducer, and the water reduction rate is 22~28%.

[0036] In the following embodiments and comparative examples, unless otherwise specified, the preparation method of the anti-seepage and anti-cracking mass concrete is as follows:

[0037] M1. Weigh each component by weight;

[0038] M2. Mix sodium acetate, modified blast furnace slag powder, 1 / 4 water reducer and 1 / 4 water for 60 to 90 seconds, then add cement, sand, crushed stone, silica fume, fly ash, tragacanth gum, 2 / 4 water reducer and 2 / 4 water, mix for 40 to 60 seconds, add expanded perlite water-absorbing aggregate, self-healing polyvinyl alcohol fiber, the remaining water reducer and water, mix for 60 to 90 seconds to obtain concrete.

[0039] Example 1

[0040] The present embodiment provides an anti-seepage and anti-cracking mass concrete, comprising the following components in parts by weight: 360 parts of cement, 70 parts of fly ash, 10 parts of silica fume, 40 parts of modified blast furnace slag powder, 5 parts of sodium acetate, 760 parts of sand, 130 parts of expanded perlite water-absorbing aggregate, 950 parts of crushed stone, 8 parts of water reducer, 140 parts of water, 2 parts of self-repairing polyvinyl alcohol fiber, and 1.4 parts of tragacanth gum;

[0041] The preparation method of modified blast furnace slag powder is as follows: blast furnace slag with a particle size of 0.1 to 5 mm and stearic acid are added into a ball mill, the mass of stearic acid is 0.3% of the mass of blast furnace slag, 20 alumina grinding balls are installed in the ball mill, and the ball mill rotates at 200 rpm / min for 60 minutes, and the specific surface area is ≥360m after screening. 2 / kg of modified blast furnace slag powder.

[0042] The preparation method of expanded perlite water-absorbing aggregate comprises the following steps:

[0043] S1. The corn gluten was dissolved in 85% ethanol aqueous solution, diethyl phthalate was added, and the mixture was stirred to obtain a hydrophobic coating solution; the mass ratio of corn gluten, 85% ethanol aqueous solution and diethyl phthalate was 0.5:9.5:0.1;

[0044] S2. Stir the expanded perlite and mannitol at a mass ratio of 1:0.1 at 60°C for 40 minutes to wrap the mannitol on the surface of the expanded perlite to obtain coated particles; then place the coated particles in the hydrophobic coating solution of step S1 and soak for 20 minutes, take out and let stand to dry, soak again for 20 minutes, take out and let stand to dry to obtain expanded perlite water-absorbing aggregate.

[0045] The preparation method of the self-repairing polyvinyl alcohol fiber comprises the following steps:

[0046] P1. The polyvinyl alcohol fiber was rinsed with deionized water, taken out and allowed to stand for drying, and then the polyvinyl alcohol fiber was immersed in a 20% aqueous solution of gum arabic for 10 minutes, taken out and allowed to stand for 10 minutes, and then added to a mixed powder of white gum powder and magnesium fluorosilicate in a mass ratio of 100:6, and stirred evenly to obtain a core material;

[0047] P2. Dissolve polystyrene and polylactic acid in chloroform to prepare a mixed solution with a concentration of 2 wt% of polystyrene and polylactic acid; then add the core material obtained in step P1 to the mixed solution, stir for 1 hour, vacuum filter, and dry at 40°C for 1 hour to obtain a self-repairing polyvinyl alcohol fiber with an encapsulation shell layer on the surface.

[0048] Example 2

[0049] The anti-seepage and anti-cracking mass concrete of this embodiment is basically the same as that of Embodiment 1, except that the anti-seepage and anti-cracking mass concrete of this embodiment includes the following components in parts by weight: 340 parts of cement, 55 parts of fly ash, 15 parts of silica fume, 60 parts of modified blast furnace slag powder, 8 parts of sodium acetate, 720 parts of sand, 160 parts of expanded perlite water-absorbing aggregate, 900 parts of crushed stone, 5 parts of water reducer, 155 parts of water, 1 part of self-repairing polyvinyl alcohol fiber, and 0.8 parts of tragacanth gum;

[0050] The preparation method of modified blast furnace slag powder is as follows: blast furnace slag with a particle size of 0.1 to 5 mm and stearic acid are added into a ball mill, the mass of stearic acid is 0.5% of the mass of blast furnace slag, 25 alumina grinding balls are installed in the ball mill, and the ball mill rotates at 100 rpm / min for 80 minutes, and the specific surface area is ≥360m after screening. 2 / kg of modified blast furnace slag powder.

[0051] The preparation method of expanded perlite water-absorbing aggregate comprises the following steps:

[0052] S1. Dissolve corn gluten in 70% ethanol aqueous solution, add diethyl phthalate, and stir to obtain a hydrophobic coating solution; the mass ratio of corn gluten, 70% ethanol aqueous solution and diethyl phthalate is 1.0:9.5:0.2;

[0053] S2. Stir the expanded perlite and mannitol at a mass ratio of 1:0.2 at 70°C for 30 minutes to wrap the mannitol on the surface of the expanded perlite to obtain coated particles; then place the coated particles in the hydrophobic coating solution of step S1 and soak for 30 minutes, take out and let stand to dry, soak again for 30 minutes, take out and let stand to dry to obtain expanded perlite water-absorbing aggregate.

[0054] The preparation method of the self-repairing polyvinyl alcohol fiber comprises the following steps:

[0055] P1. The polyvinyl alcohol fiber was rinsed with deionized water, taken out and allowed to stand for drying, and then the polyvinyl alcohol fiber was immersed in a 30% aqueous solution of gum arabic for 20 minutes, taken out and allowed to stand for 15 minutes, and then added to a mixed powder of white gum powder and magnesium fluorosilicate in a mass ratio of 100:8, and stirred evenly to obtain a core material;

[0056] P2. Dissolve polystyrene and polylactic acid in chloroform to prepare a mixed solution with a concentration of 1 wt% of polystyrene and polylactic acid; then add the core material obtained in step P1 to the mixed solution, stir for 1 hour, vacuum filter, and dry at 37°C for 1.5 hours to obtain a self-repairing polyvinyl alcohol fiber with an encapsulation shell layer on the surface.

[0057] Comparative Example 1

[0058] The concrete of Comparative Example 1 is substantially the same as that of Example 1, except that blast furnace slag powder is used in this comparative example instead of modified blast furnace slag powder, and the amount used remains unchanged.

[0059] Comparative Example 2

[0060] The concrete of Comparative Example 2 is substantially the same as that of Example 1, except that expanded perlite is used in this comparative example instead of expanded perlite water-absorbing aggregate, and the amount used remains unchanged; before use, the expanded perlite is soaked in water for 10 to 12 hours to make it saturated with water.

[0061] Comparative Example 3

[0062] The concrete of comparative example 3 is substantially the same as that of example 1, except that polyvinyl alcohol fiber is used in this comparative example instead of self-repairing polyvinyl alcohol fiber, and the amount used remains unchanged.

[0063] Comparative Example 4

[0064] The concrete of Comparative Example 4 is substantially the same as that of Example 1, except that this comparative example lacks sodium acetate.

[0065] Comparative Example 5

[0066] The concrete of Comparative Example 5 is substantially the same as that of Example 1, except that the preparation method of the expanded perlite water-absorbing aggregate is as follows:

[0067] S1. The corn gluten was dissolved in 85% ethanol aqueous solution, diethyl phthalate was added, and the mixture was stirred to obtain a hydrophobic coating solution; the mass ratio of corn gluten, 85% ethanol aqueous solution and diethyl phthalate was 0.5:9.5:0.1;

[0068] S2. Soak the expanded perlite in the hydrophobic coating solution of step S1 for 20 minutes, take it out and let it stand to dry, soak it again for 20 minutes, take it out and let it stand to dry.

[0069] That is, compared with Example 1, this comparative example lacks mannitol.

[0070] Comparative Example 6

[0071] The concrete of Comparative Example 6 is substantially the same as that of Example 1, except that the preparation method of the self-repairing polyvinyl alcohol fiber is as follows:

[0072] P1. The polyvinyl alcohol fiber was rinsed with deionized water, taken out and dried, and then the polyvinyl alcohol fiber was immersed in a 20% aqueous solution of gum arabic for 10 minutes, taken out and allowed to stand for 10 minutes, and then added to the white gum powder and stirred to obtain a core material;

[0073] P2. Dissolve polystyrene and polylactic acid in chloroform to prepare a mixed solution with a concentration of 1 wt% of polystyrene and polylactic acid; then add the core material obtained in step P1 to the mixed solution, stir for 1 hour, vacuum filter, and dry at 40°C for 1 hour to obtain a self-repairing polyvinyl alcohol fiber with an encapsulation shell layer on the surface.

[0074] That is, compared with Example 1, this comparative example lacks magnesium fluorosilicate.

[0075] Test example

[0076] The concrete of the embodiment and the comparative example was tested for working performance, mechanical properties, hydrophobicity, crack resistance and impermeability. The test results are shown in Table 1.

[0077] According to the provisions of GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", the working performance of the freshly mixed concrete of the embodiments and comparative examples was tested; the mechanical properties of the concrete were tested according to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Ordinary Concrete"; the water contact angle of the concrete was tested using a contact angle meter to determine the hydrophobic effect of the concrete. The internal contact angle detection method was to cut the concrete sample, smooth it with sandpaper, blow off the surface dust, and then detect the contact angle.

[0078] According to GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", the early crack resistance and impermeability of concrete are tested. The "anti-crack plate test" is used to measure the early crack resistance of concrete. The test results are expressed as the total crack area per unit area calculated. The smaller the value, the better the crack resistance. The "seepage height method" is used to measure the average seepage height of concrete under constant water pressure, which is expressed as the concrete water penetration resistance. The larger the average seepage height of the specimen, the worse the water penetration resistance of the specimen.

[0079] Table 1 Concrete performance test results

[0080]

[0081] From the test results in Table 1, it can be seen that in terms of workability, the slump of Examples 1 to 2 is 210mm, which has relatively good workability. During the test, the cohesiveness and water retention of the concrete are also good. In terms of mechanical properties, the 28d compressive strength of Examples 1 to 2 is greater than 55MPa, which has excellent compressive strength. The internal and external water contact angles of Examples 1 to 2 are both ≥142°, and the internal and external water contact angles are basically the same. The concrete of the present invention has good overall hydrophobic performance. According to the early crack resistance flat plate test results, the total crack area per unit area of ​​Examples 1 to 2 is 32mm 2 / m 2Within 3000 mm, almost no cracks can be observed on the surface of the flat plate with the naked eye, and the anti-cracking performance is excellent; in terms of anti-seepage performance, the water seepage height of Examples 1 to 2 is around 26.2 to 26.5 mm under constant water pressure, the water seepage height is relatively small, and the overall anti-seepage performance of the concrete is outstanding.

[0082] Compared with Example 1, Comparative Example 1 uses blast furnace slag powder instead of modified blast furnace slag powder. When blast furnace slag powder is added to concrete, the total amount of adhesive powder increases, the slump of concrete decreases to 180 mm, and the flowability deteriorates; blast furnace slag powder has better secondary hydration effect than modified blast furnace slag powder, so the compressive strength is improved, but the risk of cracking is also increased, and the total cracking area per unit area is increased to 89 mm 2 / m 2 In addition, the water contact angle decreased by 21.6%, the overall hydrophobicity of the concrete decreased significantly, and at the same time, the water seepage height of the concrete increased significantly, and the overall anti-permeability performance of the concrete decreased.

[0083] Compared with Example 1, Comparative Example 2 uses water-saturated expanded perlite instead of expanded perlite water-absorbing aggregate. The water-saturated expanded perlite releases water slowly in the internal space of the dense concrete after solidification, and the water absorption effect cannot be guaranteed. The water seepage height method is used for testing. Water is pressed into the interior of the concrete from the bottom by pressure. Since the expanded perlite is relatively saturated with water, it does not have good water absorption characteristics and cannot form the effect of delaying the upward infiltration of water. Therefore, the final water seepage height is 39.8 mm, which is 13.6 mm higher than that of Example 1. It shows that the use of the expanded perlite water-absorbing aggregate of the present invention can achieve a relatively excellent anti-seepage effect in the concrete service stage, preventing water from leaking to the inner wall.

[0084] Compared with Example 1, Comparative Example 3 uses polyvinyl alcohol fiber instead of self-repairing polyvinyl alcohol fiber. The surface of ordinary polyvinyl alcohol fiber is not treated, and the bonding strength with concrete is slightly lower, so the total crack area per unit area increases, and the early crack resistance is reduced. In order to verify the self-repairing effect of self-repairing polyvinyl alcohol fiber, a new test method is designed for verification on the basis of conventional flat plate crack resistance test. The difference between it and the conventional flat plate crack resistance test is mainly that: it is divided into two crack readings. The first crack reading is 48 hours after the concrete is stirred and water is added. After the reading is completed, 4 to 5 cm of water is added to the concrete surface of the anti-cracking plate. After standing for 7 days, the crack is read again. According to the total crack area per unit area before and after, the crack repair rate is calculated. Through detection and calculation, it is found that the crack repair rate of Example 1 is ≥78%, while the crack repair rate of Comparative Example 3 is <10%, which shows that the self-repairing polyvinyl alcohol fiber of the present invention has effective crack repair ability and can greatly improve the crack resistance and impermeability of concrete.

[0085] Compared with Example 1, Comparative Example 4 lacks sodium acetate, and the 28d compressive strength decreases by 5.5 MPa, the water contact angle decreases by about 12%, and the water seepage height increases by 35.5%, which indicates that sodium acetate can improve the hydrophobicity of concrete, thereby improving the anti-permeability of concrete. At the same time, because there is no introduction of sodium acetate, the blast furnace slag powder cannot be effectively stimulated to form more CSH gel and ettringite (AFt) crystals to fill the pores and improve the density of concrete, so the compressive strength is reduced.

[0086] Compared with Example 1, Comparative Example 5 lacks mannitol, the 28d compressive strength is reduced, and the water seepage height is increased. This is because the complexation of mannitol can fill the gap between the expanded perlite and the cement-based interface, optimizing and improving the strength and compactness of the concrete. In terms of crack resistance, the total cracking area per unit area of ​​Comparative Example 5 increases, and the crack resistance deteriorates. This may be because mannitol can reduce the hydration heat release and reduce the concrete temperature shrinkage cracking. In order to further verify the heat absorption and cooling effect of mannitol, the concrete adiabatic temperature rise tester was used to measure the adiabatic temperature rise temperature of the concrete. The test results show that the concrete temperature rise of Example 1 is reduced by 7.4°C compared with Comparative Example 5. This shows that mannitol can reduce the cement-based hydration heat release and effectively reduce the internal temperature rise and shrinkage cracking of large-volume concrete.

[0087] Compared with Example 1, Comparative Example 6 lacks magnesium fluorosilicate. The crack repair rate was calculated using the method for verifying the self-repairing effect of self-repairing polyvinyl alcohol fiber. Through testing, it was found that the crack repair rate of Comparative Example 6 was 51%, which was much lower than 78% of Example 1. Using a 50x electron microscope, it was found that the white gel in some wider cracks was relatively dispersed and lacked strength, which proved that magnesium fluorosilicate promoted the Ca in concrete. 2+ The dissolution of Ca 2+ It interacts with the hydroxyl groups in the white radish glue to form ionic crosslinks, thereby increasing the strength of the gel formed by the white radish glue, effectively promoting the white radish glue to seal cracks and slow down stress expansion.

[0088] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A kind of anti-seepage and anti-cracking mass concrete, characterized in that: The invention comprises the following components in parts by weight: 410-440 parts of cementitious material, 40-60 parts of modified blast furnace slag powder, 5-8 parts of sodium acetate, 720-760 parts of sand, 130-160 parts of expanded perlite absorbent aggregate, 900-950 parts of crushed stone, 5-8 parts of water reducer, 140-155 parts of water, 1-2 parts of self-repairing polyvinyl alcohol fiber, and 0.8-1.4 parts of tragacanth gum; The modified blast furnace slag powder is obtained by mixing blast furnace slag and stearic acid and then ball milling; The preparation method of the expanded perlite water-absorbing aggregate comprises the following steps: S1. Dissolve corn gluten in an ethanol solution, add a plasticizer, and stir to obtain a hydrophobic coating solution; S2. The expanded perlite and mannitol were mixed at 60 to 70 ° C, so that mannitol was coated on the surface of the expanded perlite to obtain coated particles, and then the coated particles were immersed in the hydrophobic coating solution of step S1, and the expanded perlite was taken out and dried to obtain the water-absorbing aggregate; The preparation method of the self-repairing polyvinyl alcohol fiber has the following steps: soaking the polyvinyl alcohol fiber in an arabic gum aqueous solution, taking it out and adding it into a mixed powder of white gum and magnesium fluorosilicate, stirring it evenly, taking it out and then using a polystyrene and polylactic acid blend for surface encapsulation to obtain the obtained fiber.

2. The anti-seepage and anti-cracking mass concrete according to claim 1, characterized in that: The mass of the stearic acid is 0.3% to 0.5% of the mass of the blast furnace slag.

3. The anti-seepage and anti-cracking mass concrete according to claim 1, characterized in that: In step S1, the mass ratio of the corn protein, the ethanol solution and the plasticizer is (0.5-1.0):9.5:(0.1-0.2), and the mass concentration of the ethanol solution is 60%-92%.

4. The anti-seepage and anti-cracking mass concrete according to claim 1, characterized in that: In step S2, the mass ratio of the expanded perlite to mannitol is 1:(0.1-0.2).

5. The anti-seepage and anti-cracking mass concrete according to claim 1, characterized in that: In step S2, the coated particles are placed in a hydrophobic coating solution and soaked for 20 to 30 minutes, taken out and allowed to stand and dry, and then soaked again for 20 to 30 minutes, taken out and allowed to stand and dry to obtain the expanded perlite water-absorbing aggregate.

6. The anti-seepage and anti-cracking mass concrete according to claim 1, characterized in that: The mass ratio of the bletilla striata glue to magnesium fluorosilicate is 100:(6-8).

7. The anti-seepage and anti-cracking mass concrete according to claim 1, characterized in that: The cementitious material comprises cement, fly ash and silica fume in a mass ratio of (340-360):(55-70):(10-15).

8. The method for preparing a seepage-proof and crack-resistant mass concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: M1. Weigh each component by weight; M2. The sodium acetate, modified blast furnace slag powder, 1 / 4 water reducer and 1 / 4 water are mixed evenly, and then the cementitious material, sand, gravel, tragacanth gum, 2 / 4 water reducer and 2 / 4 water are added and mixed evenly, and then the expanded perlite water-absorbing aggregate, self-healing polyvinyl alcohol fiber, 1 / 4 water reducer and 1 / 4 water are added and mixed evenly to obtain concrete slurry.